Effects of Molecular Structure on Organic Contaminants’ Degradation Efficiency and Dominant ROS in the Advanced Oxidation Process with Multiple ROS - Xie, Zhi-Hui; He, Chuan-Shu; Zhou, Hong-Yu; Li, Ling-Li; Yang Liu; Du, Ye; Liu, Wen; Mu, Yang; Bo Lai (Environmental Science & Technology, 2022)
In this study, the previously overlooked effects of contaminants’ molecular structure on their degradation efficiencies and dominant reactive oxygen species (ROS) in advanced oxidation processes (AOPs) are investigated with a peroxymonosulfate (PMS) activation system selected as the typical AOP system. Averagely, degradation efficiencies of 19 contaminants are discrepant in the CoCaAl-LDO/PMS system with production of SO4•–, •OH, and 1O2. Density functional theory calculations indicated that compounds with high EHOMO, low-energy gap (ΔE = ELUMO – EHOMO), and low vertical ionization potential are more vulnerable to be attacked. Further analysis disclosed that the dominant ROS was the same one when treating similar types of contaminants, namely SO4•–, 1O2, 1O2, and •OH for the degradation of CBZ-like compounds, SAs, bisphenol, and triazine compounds, respectively. This phenomenon may be caused by the contaminants’ structures especially the commonly shared or basic parent structures which can affect their effective reaction time and second-order rate constants with ROS, thus influencing the contribution of each ROS during its degradation. Overall, the new insights gained in this study provide a basis for designing more effective AOPs to improve their practical application in wastewater treatment.